Chemical Properties of Soil of Marly Lands with Different Erosion Types in Northern Iran - BakhshiPour, Ramzan; Ramezanpour, Hassan; Esmaeelnezhad, Leila (Asian Journal of Chemistry, 2010)
In this investigation after field surveying, soil sampling were carried out from top soil of different erosional forms of marly lands including sheet, rill, gully and badlands (12 samples from 0-30 cm of each one) and from subsoil of gully and badlands (12 samples from the lowest depth of each one). These marly lands which located on the northern Iran have aridic moisture regime and thermic temperature regime. Comparing the average of chemical factors with different type of erosion by using Duncan test showed that amounts of EC (electrical conductivity), exchangeable and soluble sodium, SAR (sodium adsorption ratio) and ESP (exchangeable sodium per cent) had significant difference (p < 0.05) between all forms of erosion. While, CaCO3, gypsum, calcium, magnesium, potassium, HCO3–, SO42-, Cl– had no significant effect in form and type of erosion. Also, the comparison of mean for CEC (cation exchange capacity), pH and organic carbon revealed that sheet erosion as well as rill erosion had significant difference (p < 0.05) with other forms of erosion (gully and badland erosion).